Efektivitas Terapi Musik Degung Sunda Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi - Lia Mulyati; Rany Muliany Sudirman (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2017)
Hypertension is a degenerative disease that becomes an important health problem can cause various complications for the sufferer of one of the stress factors that affect through through the activation of hypotalamic-pituitary axis. Music therapy is one of the non-pharmacological techniques that has the effect of relaxation, which can affect the hypothalamic-pituitary-and adrenal mechanisms. Degung sunda one of the traditional musical instruments has a regular rhythm and rhythm that has a meditative impact. The objective of the study was to identify the effectiveness of Sundanese music therapy on the decrease of blood pressure in hypertensive patients in Pancalang sub-district, Kuningan Regency. Types of quasi experimental research with nonequivalent control group design. Sampling by purposive sampling technique 50 people with paired t-test data analysis. The results of music therapy therapy degu sunda can lower blood pressure, especially in systolic blood pressure (p value 0.02). There was a significant mean difference between systolic blood pressure in the control group and the intervention and no significant difference in mean diastolic blood pressure in the control group and intervention, Sundanese music therapy can lower blood pressure, especially in systolic blood pressure. The need for improved preventive health services in the form of counseling and health education with the provision of degener music intervention in patients with hypertension.